Forecasting Renewable Energy Transition Using Error Correction Model: Addressing Environmental and Sustainable Development - Nisa, Hoerun; Rachmawatie, Dessy; Ziat, Younes; Wardani, Dyah Titis Kusuma (Universitas Diponegoro, 2026)
In the context of global warming, the transition from fossil fuels to renewable energy is crucial for reducing carbon emissions and achieving sustainable development goals. From 1990 to 2022, this study examines new energy consumption in Indonesia and examines its relationship with GDP, foreign direct investment (FDI), urbanization, carbon emissions (CO2), the exchange rate, and subsidies received. An ECM was used to determine the short- and long-term impacts. In the short term, economic growth has a positive and significant effect on energy consumption; however, in the long term, the negative effect becomes more pronounced. Direct investment (FDI) has no significant effect on renewable energy consumption, creating a negative long-term trend. Urbanization has significant positive and negative dampening effects on new energy consumption in the long term, but no significant short-term effects. Energy consumption and carbon emissions have a significant negative effect. To solve construction and environmental challenges in Indonesia, it is necessary to increase the capacity of renewable energy sources.